Dynamic characteristics of a high-speed train gearbox in the vehicle–track coupled system excited by wheel defects. (November 2020) - Wang, Zhiwei; Allen, Paul; Mei, Guiming; Yin, Zhonghui; Cheng, Yao; Zhang, Weihua
To analyse and simulate the dynamic responses of the gearbox in a vehicle–track system, a three-dimensional vehicle–track coupled dynamics model for high-speed trains has been developed in this study with a comprehensive consideration of the transmission system. Using this dynamics model, the coupling effects between the gearbox housing and its connected components were analysed. Based on the dynamic results, the dynamic stress field of the gearbox housing can be obtained using the finite element methods. The model outputs were successfully validated through comparisons with field test data. Following model validation, the dynamic stress and its distribution throughout the gearbox housing were further investigated under different excitations, including track irregularities, wheel polygonal wear and flatness. The results demonstrate a significant increase in the stress levels of the oil level window aperture and the bottom face of the housing, which coincides with the location of cracks that are formed in the gearbox housing during frequent vehicle operation. While a specific case has been studied here, the proposed dynamics model can be applied to related dynamic assessments, such as vibration or suspension parameter analyses, as well as to stress analyses of any rail vehicle transmission system to guide the maintenance and design.